Synthesis and characterization of F doped ZnO nanopowders by chemical routes of co-precipitation and sonochemical process - Chatpong Bangbai; Titarat Thongpradith; Wisanu Pecharapa; Wanichaya Mekprasart (My University, 2018)
Zinc oxide (ZnO) is an n-type semiconductor material at room temperature which a good absorber in UV region and used in many applications, such as photocatalyst and gas sensor. In this work, ZnO nanopowders were synthesized by chemical routes; co-precipitation and sonochemical method. To improve ZnO nanopowders in optical and electrical properties, fluorine (F) was doped with varied concentration from 0-9 mol%. Zinc nitrate and ammonium fluoride were used as precursor material in both processes. Ammonia solution was dropped in the solution relating to white colloidal solution. Crystalline structure in hexagonal structure of F doped ZnO was identified by X-ray diffraction (XRD). Morphology and chemical element in F doped ZnO were monitored by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). For optical and electrical properties, F doped ZnO particles were analyzed by UV-Visible spectroscopy and four point probe method, respectively. XRD pattern of ZnO structure after F doping with high crystallinity was similar to pure ZnO and obtained by both processes after annealing treatment beyond specific temperature. F doped ZnO morphologies were formed in rod-like structure by co-precipitation method. The increase of rod length was related by adding F doping concentration in ZnO matrix. Meanwhile, F doped ZnO products were formed in spherical structure with same crystallite size and particle size by sonochemical method due to the effect of ultrasound energy in the system. The improvement of optical and electrical properties in F doped ZnO was drastically obtained by co-precipitation method. The decreases of optical bandgap and electrical resistivity by F doped ZnO with co-precipitation method was occurred at 1 and 5 mol% F dopant. The influence of fluorine on ZnO structure was resulted in the defect level in band diagram and rod-like relating to narrow bandgap energy and good conductivity in ZnO.
Keywords: Ammonium fluoride; Zinc nitrate; Coprecipitation; Energy-dispersive X-ray spectroscopy; ZnO doping and properties